2021
DOI: 10.1016/j.phro.2021.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Image contrast assessment of metal-based nanoparticles as applications for image-guided radiation therapy

Abstract: Metal-based nanoparticles (NPs) have been extensively studied for dose enhancement applications in radiation therapy. This study investigated the utility of such NPs for image-guided radiation therapy (IGRT). Phantom images of gold NPs (AuNPs) and titanium peroxide NPs (TiOxNPs) with different concentrations were acquired using IGRT modalities, including cone-beam computed tomography (CBCT). AuNPs induced strong contrast enhancement in kV energy CBCT images, whereas TiOxNPs at high concentrations showed weak b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…For example, Nakayama et al demonstrated that the CT number of TiO2 NPs with a concentration of 2.0 mg/mL was about 3 HU, which is almost the same as that of water [30]. In another report by the same group using H2O2-modified TiO2 NPs, the image contrast at a concentration of 10 mg/mL could be improved depending on the CT window width and level [46]. Another study showed that TiO2 NPs with a very high concentration of 231 mg/mL had a CT number of 281.5 HU [47].…”
Section: Contrast Enhancement In Ct Imagesmentioning
confidence: 99%
“…For example, Nakayama et al demonstrated that the CT number of TiO2 NPs with a concentration of 2.0 mg/mL was about 3 HU, which is almost the same as that of water [30]. In another report by the same group using H2O2-modified TiO2 NPs, the image contrast at a concentration of 10 mg/mL could be improved depending on the CT window width and level [46]. Another study showed that TiO2 NPs with a very high concentration of 231 mg/mL had a CT number of 281.5 HU [47].…”
Section: Contrast Enhancement In Ct Imagesmentioning
confidence: 99%